2018
DOI: 10.1177/1934578x1801301204
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activities of Curcuma Genus against Hepatitis C Virus

Abstract: Hepatitis C virus (HCV) infection is one of the major public health problems in the world. Even though the new agents are shown to increase the sustained virology response, however, there are still many people who cannot access the therapy due to the high cost. Moreover, the emergence of resistance and side effects presented the necessity to develop alternative treatment agents for HCV infection. Plants of the genus of curcuma are popular among traditional medicines in the world, including Indonesia. They have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 28 publications
0
24
0
2
Order By: Relevance
“…amada), show strong cytotoxicity in a leukaemic cell line and in peripheral blood mononuclear cells, as well as having antioxidant and haemolysis properties [41]. Dry extracts from rhizomes of C. xanthorrhiza and C. zedoaria have been shown to have anticancer and antiviral properties [42][43][44]. Furthermore, volatile oils extracted from leaves of C. caesia have broad antioxidant, antiinflammatory and antimicrobial effects in vitro [45,46].…”
Section: Recent Publications On the Ginger Familymentioning
confidence: 99%
“…amada), show strong cytotoxicity in a leukaemic cell line and in peripheral blood mononuclear cells, as well as having antioxidant and haemolysis properties [41]. Dry extracts from rhizomes of C. xanthorrhiza and C. zedoaria have been shown to have anticancer and antiviral properties [42][43][44]. Furthermore, volatile oils extracted from leaves of C. caesia have broad antioxidant, antiinflammatory and antimicrobial effects in vitro [45,46].…”
Section: Recent Publications On the Ginger Familymentioning
confidence: 99%
“…[31][32][33] Extracts of C. xanthorrhiza have previously been demonstrated to exhibit anti-hepatitis C virus activity. 34 Our study showed C. xanthorrhiza has marginal inhibitory effect on HBV entry step.…”
Section: Discussionmentioning
confidence: 62%
“…is very familiar among people in Indonesia, especially this rhizome is often used as a spice in cooking and herbal/traditional ingredients. More than that, research results show that kunyit is useful as an appetite enhancer for children 12 , antioxidants and antimicrobial 48 , and anti-hepatitis C. 49 The rhizome of Curcuma domestica Val. is reported to contain the alkaloid, flavonoid, phenol, terpenoid, and glycoside compound groups.…”
Section: Resultsmentioning
confidence: 99%